PENGARUH LINE EXTENSION TERHADAPEKUITAS MEREK: Survei pada Pelanggan Produk Makanan Ringan Merek Gery di Sekolah Menengah Atas (SMA)/Sederajat di Kecamatan Pacet Kabupaten Bandung - Dini Sri Wahyuni, - (2010)
Competition increased of the food industry this can be seen from the increasing number of food products offered to consumers. In 2009 food and drink industry increased by 17.5% from 2008. Competition in the product snack food that the higher the demand the company to find out the brand equity it has. Therefore Garudafood company as the manufacturer of snack foods Gery brand to line extension activities with the aim to expand its product line and has a diverse product so that consumers can know the brand and brand equity increases of brand Gery. Based on this, the purpose of this research is conducted to know the description of line extension consists of the dimensions of form, size, packaging and taste, brand equity consists of the dimensions of brand salience, brand performance, brand imagery, brand judgment, brand feelings, and brand resonance, and how much influence line extensions on brand equity on brand snack products Gery. This study is descriptive, verification, and the method used is explanatory survey with proporsionate stratified random sampling technique, the obtained sample size of 100 respondents. The population of this research is the consumer brand snack Gery in high school or equivalent in District Pacet Bandung regency. The data used are primary and secondary data through observation, literature study, questionnaire, and to know the size of the influence of line extensions on brand equity Path analysis was used SPSS 17.0. The result states that the line extension has the effect of (68,4%) of brand equity. From the results of research on hypothesis testing can be seen that line extensions have a positive impact on brand equity.